Performance analysis of heuristic optimization algorithms for demand side energy scheduling with TOU pricing - R. Das, Nilima; C.Rai, Satyananda; K.Nayak, Ajit (International Journal of Engineering and Technology, 2018)
The major objective of the paper is to find a suitable optimization algorithm which can manage the energy consumption behaviour of a consumer in presence of time of use (TOU) pricing tariff so that the demand for energy during peak hours as well as the cost of energy for the consumer is minimized. A mathematical model has been presented to describe the proposed demand management system and a comparative assessment of the performance of different heuristic optimization algorithms for optimization of daily energy consumption of a household has also been made. The algorithm PSO and some of its variants are taken for comparison. The comparative assessment of the algorithms reveals that the NQPSO optimization algorithm which is a quantum based variant of PSO is the best among the discussed algorithms and can be implemented in a residential sector for energy optimization. From the comparison of energy costs with or without optimization it becomes apparent that the projected heuristic based optimization should be used to have an optimized schedule for the operations of the appliances at a household. As a result the individuals are motivated to be a part of the demand side energy management programs which finally leads to a reliable and stable grid system.Â Â
Keywords: APSO; IQPSOS; NQPSO; PSO; TOUP.